Code Switching Used By The Characters In The One Fine Day Film - Puspadewi, I Dewa Ayu Tri; Maharani , Sang Ayu Isnu; Saientisna, Made Detriasmita (Universitas Pahlawan Tuanku Tambusai, 2024)
This research is entitled Code Switching Used by Characters in the One Fine Day film. Code switching is a term in the field of linguistics that refers to the use of more than one language or variations in conversation. This research aims to identify various types of code switching and explain how the code switching functions are used by the characters. Poplack's theories and Appel and Muysken theories were used as a basis for designing this research. This research uses primary data in the form of a film entitled